The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3856/vol48-issue4-fulltext-2452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density on growth, survival and condition factor in tropical gar (Atractosteus tropicus Gill, 1863) juveniles

Abstract: Tropical gar (Atractosteus tropicus) is currently exploited regionally as food and commercialized in the aquarium trade. Natural populations of A. tropicus may already be negatively affected by anthropogenic alteration of the areas in which it is distributed. However, it is necessary to deepen the knowledge for the optimization of its culture. A. tropicus cultured in three stocking densities: 100, 200, and 300 ind m-3 (D4, D8, and D12, respectively) were used in the present study to examine the effect on growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…Furthermore, high density would imply high feces production that harms the water quality of the fish rearing media. High fish density was not able to provide adequate feed for tropical gar (Atractosteus tropicus) juveniles (Martínez-Cárdenas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high density would imply high feces production that harms the water quality of the fish rearing media. High fish density was not able to provide adequate feed for tropical gar (Atractosteus tropicus) juveniles (Martínez-Cárdenas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While in Pacific salmon, the survival rate increases according to fish age. Survival rate values approaching 100% are closely related to the good water environment and quality as well as contained biomass and ideal fish density (Ronald et al 2014;Martínez-Cárdenas et al 2020). In blue tilapia, it was shown that bigger-sized juveniles tended to have better body conditions compared to the smaller-sized juveniles (Robisalmi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although cichlids are known for their aggressive behavior, native fish species of different taxonomical groups that are currently being studied for commercial purposes have also shown similar results. Martínez-Cárdenas et al (2020)…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, greater interest and efforts to increase aquaculture production of tropical gar have been placed due to the reduced capture of this species in the natural environments [28,29]. These efforts have been translated in a broader knowledge on the optimal rearing conditions and husbandry practices [23,24,[38][39][40][41][42]. The optimal rearing temperature is 26-28 • C (Álvarez-González et al, unpublished results); thus, an alteration of just 4 • C seemed to be a quite realistic approach to explore the effects of a heat wave, considering that broader thermal alterations were registered in freshwater bodies [43].…”
Section: Discussionmentioning
confidence: 99%